Several Technical Considerations for Taking the (Paper-and-Pencil-Based) TOEFL Test - Sulistyo, Gunadi Harry (TEFLIN Journal, 2015)
The present article aims at presenting several points-commonly not realized by potential TOEFL test takers-that may be utilized to take the paper-and-pencil TOEFL. To these ends, several topics will be presented covering mainly the test format and the scoring scheme. It is under these topics that several technical strategies are discussed with the perspectives on successful paper-based TOEFL test taking.